1997
DOI: 10.1002/pro.5560060902
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of bovine chymotrypsin and trypsin complexed to the inhibitor domain of alzheimer's amyloid β‐protein precursor (APPI) and basic pancreatic trypsin inhibitor (BPTI): Engineering of inhibitors with altered specificities

Abstract: The crystal structures of the inhibitor domain of Alzheimer's amyloid @-protein precursor (APPI) complexed to bovine chymotrypsin (C-APPI) and trypsin (T-APPI) and basic pancreatic trypsin inhibitor (BPTI) bound to chymotrypsin (C-BPTI) have been solved and analyzed at 2.1 A, 1.8 A, and 2.6 A resolution, respectively. APPI and BPTI belong to the Kunitz family of inhibitors, which is characterized by a distinctive tertiary fold with three conserved disulfide bonds. At the specificity-determining site of these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 76 publications
8
129
0
3
Order By: Relevance
“…8)-In addition to PN2KPI loop 1 amino acids (Figs. 5-7), the loop 2 region amino acid, Phe 34 , was also replaced with Ala, resulting in an 8-fold loss of activity (IC 50 of 9.85 nM) as compared with WT PN2KPI (IC 50 of 1.28 nM), which agrees with the loss of activity in the APTT assay (Fig. 8, A and B).…”
Section: Purification and Characterization Of Pn2kpi Wt And Mutantsupporting
confidence: 76%
See 1 more Smart Citation
“…8)-In addition to PN2KPI loop 1 amino acids (Figs. 5-7), the loop 2 region amino acid, Phe 34 , was also replaced with Ala, resulting in an 8-fold loss of activity (IC 50 of 9.85 nM) as compared with WT PN2KPI (IC 50 of 1.28 nM), which agrees with the loss of activity in the APTT assay (Fig. 8, A and B).…”
Section: Purification and Characterization Of Pn2kpi Wt And Mutantsupporting
confidence: 76%
“…After surveying all of the serine protease structures in complex with APPI and BPTI in the Protein Data Bank, we observed that Glu/Gln 192 of the serine protease forms either no hydrogen bond or one hydrogen bond with the carbonyl oxygen atom of Cys 14 (P2) of APPI or BPTI. In the structure of FVIIa with a BPTI mutant (Protein Data Bank code 1FAK (37)), which mimics the first Kunitz domain of tissue factor pathway inhibitor (the natural inhibitor of the tissue factor FVIIa complex), Lys 192 is hydrogen-bonded to Asp 11 (a mutated residue, T11D) and the carbonyl oxygen atom of Tyr 34 (V34Y) of the BPTI mutant. We suspect that Lys 192 plays an important role in FXIa activity and is essential for the interaction between FXIa and PN2KPI.…”
Section: Conformations Lysmentioning
confidence: 99%
“…4, intact APPI is a 57-amino acid peptide featuring three internal disulfide bonds and the N-terminal sequence EVCSE. The reactive site bond identified in crystal structures of APPI bound to FXIa (33) and trypsin (39,40) is located between Arg 13 and Ala 14 (indicated by a black arrow in Fig. 4); from here on, we will refer to this bond as the Arg 15 -Ala 16 bond, according to its alignment with the archetypal Kunitz family inhibitor BPTI and for consistency with the bulk of prior literature.…”
Section: Identification Of App As a Mesotrypsinmentioning
confidence: 72%
“…tive site of APPI. Crystal structures indicate that the majority of contacts between APPI and trypsins are formed by the P 4 -P 3 Ј residues Gly-Pro-Cys-Arg-Ala-Met-Ile (39,40). We synthesized a peptide recapitulating this sequence, but substituting the P 2 Cys with Ser to prevent peptide dimerization and adding a Tyr residue at the P 4 Ј C terminus to facilitate peptide quantification.…”
Section: Identification Of App As a Mesotrypsinmentioning
confidence: 99%
“…The bovine pancreatic trypsin inhibitor belongs to the Kunitz-type inhibitors and is a potent inhibitor of serine proteases. The crystal structures of BPTI with bovine trypsin and with bovine chymotrypsin have been determined [47][48][49]. Analysis of these complexes have shown that there are 10-13 residues on the inhibitor forming less than 4 Å contacts with 20-25 residues of the enzyme.…”
Section: Page 7 Of 22mentioning
confidence: 99%